An unusual histopathologic feature of angiomatoid fibrous histiocytoma - A case report and molecular study - Yeh-Ni Chu; Chih-Jung Chen; Cher-Wei Liang; Hsiu-Cheng Hsu (Wolters Kluwer Medknow Publications, 2018)
Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor with intermediate malignant potential. It predominantly affects children and young adults and is most often located in the extremities. The atypical pattern of AFH may create significant diagnostic difficulty. We present a case of AFH diagnosed via molecular confirmation by fluorescence in situ hybridization (FISH) and also review cases of AFH with atypical histologic presentations in Taiwan. We present this case to remind clinicians that identification of gene fusions by molecular testing is a valuable diagnostic tool for AFHs, especially in cases with atypical histopathological presentations. Keywords: Angiomatoid fibrous histiocytoma (AFH), Fluorescence in situ hybridization (FISH), Molecular testing